Reliability and fragility assessment of the mid- and high-rise wood buildings subjected to bidirectional seismic excitation. (15th December 2019) - Hong, H.P.; Yang, S.C.
Highlights: Established a simple procedure to model the capacity surface of bisymmetric building. Estimated fragility of bisymmetric building under bidirectional ground motions. Evaluated reliability of timber buildings under bidirectional ground motions. Estimated fragility surface of timber buildings under bidirectional ground motions. Abstract: Often the estimation of reliability and fragility curve for a structure subjected to earthquake loading is carried out for unidirectional ground motions, even though the multicomponent ground motions can affect the seismic responses. A simple procedure to estimate the reliability of 3D bisymmetric buildings subjected to the bidirectional orthogonal ground motions is proposed in the present study. The procedure considers that the responses of a 3D bisymmetric building can be approximated by those of an equivalent nonlinear inelastic two-degree-of-freedom (2DOF) system. The parameters of the equivalent system are identified using the capacity surface of the buildings obtained through nonlinear static pushover analysis or incremental dynamic analysis. The procedure is applied to estimate the reliability and fragility of mid- and high-rise wood buildings subjected to bidirectional ground motions. A comparison of the estimated reliabilities and fragilities by considering uni- and bi-directional ground motions is given, showing the importance of considering the bidirectional ground motions. The results indicate that the failure probabilities under the bidirectional ground motions are greater as compared to those obtained under the unidirectional ground motions. Therefore, for assessing the reliability of building under the seismic ground motions, the consideration of bidirectional ground motion can be important for seismic risk modelling and emergency preparedness.